SINONIM ADJEKTIVA UTSUKUSHII DAN KIREIDA DALAM BAHASA JEPANG: KAJIAN SEMANTIK - Intan Dwi Dahidi Putri (Jurnal Sora : Pernik Studi Bahasa Asing, 2018)
Kireida and utsukushii adjectives are synonymous adjectives, which have the same meaning in the forms of language, it is called ruigigo in Japanese language. The two adjectives in Indonesian language mean ‘beautiful/nice’. The background of chosen these two adjectives are being used in everyday Japanese life; in Japanese language textbooks. The purposes of this research are to find out the similarities and differences in utsukushii and kireida adjectives as synonyms by describing similarities and differences in terms of sentence structure, meaning and function based on the context of the sentence. In studying the similarities and differences as synonyms, sentence substitution techniques are used. The results of this research have been founded that there are similarities of utsukushii and kireida adjectives with the same meanings such as beautiful, good, loud/sweet in Indonesian based on the context of the sentence. In addition, these two adjectives are used to express a description of an object that can be seen or heard. The difference between utsukushii and kireida adjectives is in the subject or noun used. Subjects or nouns in utsukushii are abstract objects in the form of a social relationship. While the subject or noun in kireida is an abstract object in the form of a mixture of various colorless gases, concrete objects, activities, and actions.